Two Sequential Multicomponent Reactions: Synthesis of Thiazolidin-4-yl-1,3,4-oxadiazoles under Mild Conditions - Brockmeyer, Fabian; van Gerven, David; Saak, Wolfgang; Martens, Jürgen (Synthesis, 2014)
This work describes the synthesis of compounds including both thiazolidine and 1,3,4-oxadiazole heterocyclic systems. The preparation is realized following a new synthesis route consisting of two multicomponent reactions. First 3-thiazolines are formed by an Asinger four-component reaction. Conversion of these cyclic imines into α-amino-1,3,4-oxadiazoles is subsequently achieved by a three-component reaction involving (isocyanoimino)triphenylphosphorane and a carboxylic acid. The synthesis route is characterized by mild reaction conditions and it tolerates many functional groups. As shown by the conversion into urea derivatives the prepared α-amino-1,3,4-oxadiazoles are marked by their potential in subsequent reactions.
Keywords: heterocycles; imines; multicomponent reaction; ring closure; polycycles